Gestión de residuos plásticos domiciliarios en Bogotá desde la teoría de sistemas complejos (2021)
Today, constant concern about the deterioration of the environment is an issue concerning all human beings as a factor of great social relevance. The term environmental management has been welcomed in society because of the different problems that have been evident in the environment, today a term that seeks to collide with environmental management to be examined from another point of view, is the complexity, a term that has been positioned as the reflection of a knowledge previously imparted. As environmental management is a broad issue involving economic, political, social and cultural components, the present undergraduate work, of an investigative nature, focuses on understanding the management of plastic waste from the point of view of complex systems.